Pengaruh Jumlah Pemadatan dan Tebal Hamparan Terhadap Kinerja RCC (Roller Compacted Concrete) untuk Perkerasan Jalan Raya - Marjono Marjono; Mochamad sholeh; Udi Subagyo (Prokons: Jurnal Teknik Sipil, 2022)
AbstractRCC (Roller Compacted Concrete) is one of the results of innovation in the field of building materials, this material is made from a mixture of coarse aggregate, fine aggregate, cement and water in a certain ratio which is compacted by rolling. This material can be used for road pavement. RCC was chosen because it has advantages, one of which is that this material is able to produce a higher compressive strength at a young age, the pavement is smoother than conventional concrete and is not slippery so it does not need to be roughed/grooved. This advantage is needed in road pavement construction work, especially on roads that are immediately operated or implemented during the rainy season.The results showed that, with variations in the amount of compaction 12 times, 16 times, 20 times, 24 times, 32 times and 40 times, which were carried out on the thickness of the RCC. 5 cm, 6 cm and 7 cm. significant effect on the compressive strength of concrete, and the form of the equation, for a thickness of 5 cm at the age of 28 days: y = -0.0873x2 + 7.5459x + 158.83, for a thickness of 6 cm at the age of 28 days: y = -0.1403x2 + 13.33x + 86,397 and for 7 cm thick at 28 days old: y = -0.0456x2 + 5.2617x + 275.35Keywords: RCC, Roller Compacted Concrete, Road Pavement.